Bibliothécaire et médiateur culturel : le nouveau Janus du patrimoine des bibliothèques ? L’exemple de la médiation du patrimoine parisien à la Bibliothèque historique de la Ville de Paris (BHVP) - Jean-François Dubos; Morgane Menad (In Situ)
Popular with the public, particularly at major cultural events, library heritage still remains little understood. This paradoxical situation results from the necessary prerequisites to apprehend documents in all their complexity and also from the heterogeneity of the public. The heritage of public libraries, authentic collective cultural objects, should be of benefit to all in the best conditions. To this end, a mediation effort must be made both by librarians and by cultural mediators . This article examines the example of the Bibliothèque historique de la Ville de Paris, the historical library of the City of Paris, where curators and mediators are working together towards the same objectives. Results reflect the success of new practices, independent of inherent difficulties. The portrait of a new patrimonial figure emerges, a ‘biblio-médiateur’, a kind of Janus with two faces.